The characterization, persistence, and bioaccessibility of roaster-derived arsenic in surface soils at Giant Mine, Yellowknife, NT - Bromstad, MacKenzie Jane (2011)
Thesis (Master, Geological Sciences & Geological Engineering) -- Queen's University, 2011-11-22 16:16:24.721 Approximately 20,000 tonnes of arsenic (As)-bearing emissions from roasting arsenopyrite ore were aerially released from 1949-1999 at Giant Mine, located outside Yellowknife, NT. As part of the process used to free refractory gold (Au) from arsenopyrite (FeAsS), roasting created As-bearing roaster off-gases that condensed into As2O3, one of the most toxic As compounds to humans. Roaster emissions also contained some As-bearing iron (Fe)- oxides. Arsenic emission controls were first implemented in 1951, and by the time the emission control process was completely refined in 1963, 86% of the total aerial As emissions at Giant had been released into the surrounding area. The continued presence of roaster-derived As2O3 in surface soils at Giant has been previously documented despite its theoretical instability in oxidizing surface environments. Wrye (2008) found As concentrations in roaster-affected soils occurring on rock outcrop (covering ~30% of the Giant property) greater than in many other surface soils; most outcrop soils were not considered when delineating areas of contaminated material for future removal in the Giant Mine Remediation Plan (currently undergoing environmental assessment). To investigate roaster-derived As persistence, outcrop soils and soil pore waters were analyzed. Comparing proportions of As, Sb, and Au concentrations in soil samples and historic As2O3-rich dust captured by emission controls show that most of the roaster-derived As in soils at Giant was likely deposited before 1964. Thin section examination has shown that while the vast majority of discrete As hosts in soils are As2O3, textural relationships and certain secondary As hosts in soils indicate that As2O3 is not static in surface soils and could be transforming over time, albeit very slowly. Bulk chemical relationships among As, antimony (Sb), and carbon support this. Topographic restriction by rock outcrops and ...